The effectiveness of stress regulation interventions with athletes: A systematic review and multilevel meta-analysis of randomised controlled trials - Murdoch, E. M.; Lines, R. L.; Crane, M. F.; Ntoumanis, N.; Brade, C.; Quested, E.; Ayers, J.; Gucciardi, D. F. (International Review of Sport and Exercise Psychology, 2024)
We conducted a pre-registered systematic review of seven databases and meta-analysis of randomised controlled trials with athletes to examine the effectiveness of stress regulation interventions on performance outcomes, and the conditions under which their effects are strongest. We found a positive and significant moderate overall effect of stress regulation interventions on performance outcomes (65 effects, k = 21, N = 2022, g = 0.52, 95% CI = 0.19, 0.84) and a significant large effect on physiological outcomes (28 effects, k = 10, N = 368, g = 2.13, se = 0.81, 95% CI = .47, 3.79), yet the effect on psychological dimensions was statistically inconsequential (28 effects, k = 10, N = 787, g = 0.35, 95% CI = -0.12, 0.81). Sensitivity and meta-bias analyses generally supported the robustness of the pooled effect of stress regulation interventions on athlete performance, yet the prediction intervals suggested some interventions may be inefficacious or detrimental for athlete performance. The strongest effects on performance were observed at follow-up when compared with post-test. Collectively, our findings offer a high-quality assessment on the effectiveness of stress regulation interventions for athlete performance and provide direction for future research in terms of conceptual and methodological issues.